Pesantren dan Upaya Menangkal Tumbuhnya Radikalisme: Analisis Gagasan KH. Marzuki Mustamar - Salik, Mohamad; Mas'ud, Ali (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2020)
This study aims to examine the ideas of one prominent Nahdlatul Ulama (NU) figure, the leader of Pesantren Sabilurrosyad Malang named KH Marzuki Mustamar, about efforts to counteract the growth of radicalism in pesantren. Through the analysis of the interview, this study found that the most important thing in preventing the growth of radicalism in pesantren is the ability of the teacher or Kyai to contextualize the values ​​of Islamic teachings with the real context of life in the learning process. Through this ability, the students will know and understand that Islamic teachings are truly relevant to life and are able to bring benefits to all mankind. In this case, the teacher or Kyai can do in several ways: First, selecting materials or books that have moderate views based on ahlussunnah school, and reinterpreting the materials or books that are not in accordance with the Indonesian context. Second, instilling the values ​​of monotheism and human values ​​in the students in a balanced manner. Third, providing examples oftolerant behavior in society. Fourth, accustoming the students to be tolerant through direct practice to live in the community.